Soft Horrors: The Visual and Ludic Safety of Dark Cozy Games - Waszkiewicz, Agata (Replay. The Polish Journal of Game Studies, 2024)
According to their most popular definition, cozy games are characterized by visual softness and relaxing gameplay devoid of combat and time-sensitive gameplay. However, with the recent increase in popularity of these games, game developers started to experiment with genre hybridity, introducing games that combine the elements of coziness with non-cozy elements such as difficult combat or horror themes, showing a need for critical engagement with the working definition of what is cozy. The article proposes a concept of dark cozy games to describe those titles that introduce visual softness and, to some degree, ludic safety to horror or Gothic, using three examples to illustrate different ways in which that can be achieved: Cult of the Lamb, Dredge, and Oxenfree.